Optimisation of waste rock placement using mixed integer programming - Li, Y.; Topal, Erkan; Williams, D. (Maney Publishing, 2014)
Cost reduction via optimising the scheduling of waste rock placement has a very high potential of success, as large volumes of waste rock are involved in operating an open pit mine, along with high rehabilitation costs. Such scheduling must satisfy both mine planning and environmental considerations, for which mixed integer programming (MIP) models are a well suited methodology. A base MIP model, along with two variants, is created and implemented for a hypothetical mine site. Upon solving the MIP problem with more than two million possible combinations, optimised waste rock placement schedules are automatically generated. The detailed schedules will assist mine planning engineers in mine design and in improving the environmental performance of a waste rock dump.